Additional records of polynoid polychaetes from the Juan de Fuca Ridge - Pettibone, Marian H. (Proceedings of the Biological Society of Washington, 1994)
Additional specimens of two polynoid polychaetes, Bathycatalina filamentosa (Moore) (Macellicephalinae), and Harmothoe macnabi Pettibone (Harmothoniae), were collected from a new vent site on the Juan de Fuca Ridge. Based on these materials, both the subfamily Macellicephalinae and genus Bathycatalina are emended, the former to include Bathylevensteinia [sic for Bathylevinsteina] bicornis (Levenstein) and Gesiella jameensis (Hartmann-Schröder), and the descriptions of B. filamentosa and H. macnabi supplemented.
World Polychaeta Database (WPolyDb). Pettibone misspells Bathylevensteina